PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN INTERAKTIF DENGAN PLOTAGON BAGI GURU MI SA'ADATUDDARAIN II, TANGERANG - Nugroho; Mildan Arsan Fidinillah; Uup Gufron; Suwandi, Sahri; Hadi, Irfan; Eka Sanjaya, Ricky; Liska Saputri, Nia; Siregar, Nujuluddin; Purnama, Yogi; Baron, Rifari (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
The digital revolution in education requires teachers to master innovative and engaging learning technologies. This Community Service Program aims to enhance the competency of teachers at MI Sa’adatuddarain II Tangerang in creating interactive learning videos using the Plotagon application. Plotagon was chosen due to its user-friendliness and its ability to produce engaging 3D animated videos without requiring advanced technical skills. The method employed was a one-day intensive training featuring a hands-on approach, including live demonstrations, guided practice sessions, and individual mentoring. The activity was involved 25 teachers from various subjects. Pre-test results revealed a low initial knowledge level with an average score of 45.6. Following the training, this improved dramatically to an average post-test score of 82.4. Furthermore, 92% of participants successfully created simple learning videos of adequate quality, and 96% stated their intention to implement this tool in their daily teaching. Satisfaction evaluation indicated that 96% of participants were delighted with the training program. This training has proven effective in boosting teachers’ digital literacy. It holds the potential to enhance the quality of instruction at MI Sa’adatuddarain II Tangerang by utilizing more interactive and engaging media.